MENURUNKAN GANGGUAN INTERNAL DAN EKSTERNAL JARINGAN TEGANGAN MENENGAH 20 KV MELALUI METODE HEALTH INDEX DI PT PLN (PERSERO) DISTRIBUSI LAMPUNG - Burhan Nudin (Industrika : Jurnal Ilmiah Teknik Industri, 2018)
The measurement of the progress of a country with the criteria of the electric energy consumption, but this is not yet valid in Indonesia, as evidenced by the majority of Indonesian citizens who have not enjoyed it, and even if the government through PT PLN (Persero) there is a desire to raise tariff Basic Electricity (TDL) to meet the economic value, most of our society has not been able, where people still consider that the availability of electric power is still one part of infrastructure that must be provided by the state. Customer Satisfaction is very influential on the performance of PLN itself so that with all efforts PLN provide excellent service in order to reduce the number of interference network medium voltage 20 KV. Asset management is systematic and coordinated steps that are implemented optimally and continuously in managing its assets by considering the performance, cost, and risk aspects throughout the life cycle of the asset in an effort to achieve customer satisfaction objectives